Internet of Things: A Systematic Literature Review - Hashim, Hayder Salah; Hassan, Zainuddin Bin; Mohd Drus, Sulfeeza Bte (Informatica, 2022)
Abstract Internet of things (IoT) is an emerging technology that is being used widely. The literature has no agreement regarding the factors that affect the adoption of IoT. The purpose of this study is to review the literature systematically using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Following this method, 69 articles were included in this review. A frequency analysis was conducted. The findings showed that number of articles reduced during COVID19. Higher education has the highest numbers of articles. Emerging economies are active in research about IoT. Technology acceptance model (TAM) is still the dominant adoption theory with majority of the reviewed articles are using quantitative method and large sample size to meet the assumption of using structural equation modeling. The most important predictors are the perceived usefulness, perceived ease of use, social influence, privacy, security, and trust. Other factors also included the variables of UTAUT. Decision makers are recommended to focus on usefulness and simplifies the process of using IoT as well as to create awareness about the application of IoT. Future studies are recommended to narrow the scope to one industry and to conduct more studies using mixed method or qualitative approach. More studies in developing countries are needed to explain the adoption of IoT.